Aesthetic Learning by Implementing Systemic Approach to Achieve Educationional Values in Performing Arts (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
This study is aiming at developing aesthetic learning design with a systemic approach to achieve educational value in performing arts. The study was conducted by employing research development approach, consisting of stages, i.e. (1) identifying learning objectives, preceding by need assessments, (2) doing learning analysis, (3) analyzing students’ behavior and characteristics, (4) identifying specific learning objectives, (5) developing learning outcomes assessment tool, (6) developing learning strategy, (7) selecting and developing learning material, (8) designing and evaluating formative learning design, and (9) designing and conducting summative evaluations. The results of this study are a set of aesthetic learning implementation plan with a systemic approach that meets the development criteria. The aesthetic learning design has been tested and tried out; and is effectively able to achieve the learning objectives of the aesthetic course in university; namely, students are able to find the value of education in performing arts and foster aesthetic sensitivity.